Greater tree community structure complexity in sacred forest compared to reserve forest land tenure systems in eastern India. (March 2020) - Rath, Subhani; Banerjee, Subham; John, Robert
Summary: Sacred forests are small patches of forest that are preserved and protected from human exploitation. Although they are identified primarily for spiritual or religious purposes, their contribution to biodiversity conservation has been widely debated. Sacred sites are known to harbour greater biodiversity compared to exploited forests, but the patterns are not well known. We studied tree diversity in a remote forested location in eastern India where sacred forests and reserve forests used by people are present. Tree data from eight sacred forest sites and nine reserve forest sites showed that species richness was significantly greater in sacred forests; species diversity and evenness tended to be greater, but these were not statistically significant. Basal area (a measure of aboveground biomass) was significantly greater, mainly due to the greater density of large trees. There were significant departures from the theoretical expectation of stem size density distributions under pure asymmetric competition for both land tenures, which indicated that extraneous mortality increased death rates of large trees under both regimes, but sacred forests had a greater range of stem sizes. Our results suggest that sacred forests can contribute to biodiversity conservation by preserving greater tree diversity than forests subject to human use.